Natural, Ecological, and Cultural Diversity for Nepal’s Prosperity (Samsad Journal संसद जर्नल, 2025)
This paper is about Natural-Ecological-Cultural Diversity and its role for the prosperity of Nepal. The phrase “Natural-Ecological-Cultural Diversity” refers to the interconnectedness of three key aspects of diversity; natural, ecological and cultural. The natural diversity includes a variety of landscapes, ecosystems, and physical environments, such as mountains, rivers, forests, and oceans; ecological diversity includes a range of species, habitats, and ecological systems that exist within a given region, including biodiversity and the relationships between living organisms, and cultural diversity includes the richness of human traditions, languages, beliefs, practices, and ways of life that are shaped by and adapted to natural and ecological surroundings. Nepal’s rich cultural heritage, diverse ecosystems, and abundant natural resources form the foundation for sustainable national development. This paper explores the interconnected relationship between natural, ecological, and cultural diversity, emphasizing how these elements serve as invaluable resources for Nepal’s prosperity. The country’s unique geographical landscape, ranging from the Himalayas to the Tarai, fosters biodiversity that supports both traditional livelihoods and modern economic opportunities. Likewise, Nepal’s cultural diversity, shaped by indigenous knowledge systems, festivals, and heritage sites, contributes to national identity and global recognition. By integrating sustainable policies that protect the environment and promote cultural heritage, Nepal can utilize these resources to drive economic growth, tourism, and social well-being. This paper highlights the need for a balanced approach that values both conservation and development, ensuring that Nepal’s natural and cultural wealth continues to benefit future generations